Description of a new genus and species, Lhasella potala, from Xizang, China (Coleoptera: Ptinidae: Anobiinae) - Zhou, Xuan; Pubu, Zhuoma; Zhang, Wei; Shen, Rongrong; Da, Wa; Gongga, Zhaxi; Zhaxi, Pingcuo; Zahradnĺk, Petr; Bai, Ming (Zootaxa, 2025)
A new genus and species, Lhasella potala gen. nov. & sp. nov. (Ptinidae: Anobiinae: tribe incertae sedis) is described based on specimens collected from the Potala Palace in Lhasa, Xizang, China. Diagnostic characters, including the genitalia, are illustrated. Ecological observations, including photographs of habitats of the new species, are also given. A checklist of Chinese species of the family is provided. In addition, the cytochrome oxidase I (COI) barcode sequence of the new species is presented.